Downregulation of the OsAKT1 K+/Na+ Transporter Gene by CRISPR-Cas9 Mediated Transformation in Sensitive Rice IR29 Makes it Tolerant to Salt Stress (Plant Tissue Culture and Biotechnology, 2023)
The coastal area of Bangladesh is affected by soil salinity which threatens rice production. Saline soils are mainly caused by excessive Na+ which interferes with the uptake of the essential nutrient K+. Certain K+ transporters may cause leakage of Na+ ions and the OsAKT1 transporter was earlier shown to be downregulated under salt stress in a tolerant rice landrace called Horkuch. We therefore targeted this gene for Crispr-mediated downregulation by Agrobacterium-mediated in planta transformation in salt sensitive IR29 rice. The gene was shown to be significantly downregulated in at least 3 independent transformants. One of the gene edited IR29 transformants showed significantly high survival, low loss in chlorophyll content, low electrolyte leakage as well as low H2O2 after 15-days of salt stress at 120mM NaCl at the T3 generation. Therefore the potassium transporter OsAKT1 gene is a good target for downregulation to produce salt tolerant rice.Plant Tissue Cult. & Biotech. 33(1): 71-84, 2023 (June)